Survival/Adaptation of Bone Marrow-Derived Mesenchymal Stem Cells After Long-Term Starvation Through Selective Processes. (25th March 2019) - Ferro, Federico; Spelat, Renza; Shaw, Georgina; Duffy, Niamh; Islam, Md Nahidul; O'Shea, Paula M.; O'Toole, Daniel; Howard, Linda; Murphy, J. Mary
Abstract: : After in vivo transplantation, mesenchymal stem cells (MSC) face an ischemic microenvironment, characterized by nutrient deprivation and reduced oxygen tension, which reduces their viability and thus their therapeutic potential. Therefore, MSC response to models of in vitro ischemia is of relevance for improving their survival and therapeutic efficacy. The aim of this study was to understand the survival/adaptive response mechanism that MSC use to respond to extreme culture conditions. Specifically, the effect of a long-term starvation on human bone marrow (hBM)-derived MSC cultured in a chemically defined medium (fetal bovine serum-free [SF] and human SF), either in hypoxic or normoxic conditions. We observed that hBM-MSC that were isolated and cultured in SF medium and subjected to a complete starvation for up to 75 days transiently changed their behavior and phenotype. However, at the end of that period, hBM-MSC retained their characteristics as determined by their morphology, DNA damage resistance, proliferation kinetic, and differentiation potential. This survival mode involved a quiescent state, confirmed by increased expression of cell cycle regulators p16, p27, and p57 and decreased expression of proliferating cell nuclear antigen (PCNA), Ki-67, mTOR, and Nanog. In addition, Jak/STAT (STAT6) antiapoptotic activity selected which cells conserved stemness and that supported metabolic, bioenergetic, and scavenging requirements. We also demonstrated that hBM-MSC exploited an autophagic process which induced lipid β-oxidation as an alternative energy source. Priming MSC by concomitant starvation and culture in hypoxic conditions to induce their quiescence would be of benefit to increase MSC survival when transplanted in vivo. Stem Cells 2019;37:813–827 : Abstract : Key players involved in hBM-MSC survival/adaptation after long-term starvation.